Socialization of Medicinal Plant Utilization and its Development Potential for Students of Private Vocational School Al Razi Sinar Harapan Medan - Ritonga, Ahmad Hafizullah; Harahap, Hasni Yaturramadhan; Herlina, Herlina; Harefa, Karnirius; Sitorus, Rotua Sumihar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Medicinal plants have long been inseparable from Indonesia's cultural heritage and hold significant potential for developing the healthcare and economic sectors. However, the understanding of the younger generation regarding the benefits and value of medicinal plants still needs to be improved. This article examines efforts to promote the importance of medicinal plants, mainly targeted at Clinical and Community Pharmacy Study Program students at Al Razi Sinar Harapan Medan Private Vocational School. In an attempt to address this issue, promoting the benefits and potential of medicinal plants becomes crucial. The activities aim to enhance the awareness and understanding of participants about the significance of medicinal plants in the realms of healthcare and industry. The methods used in these activities include lectures, group discussions, practical demonstrations, and evaluations. These promotion activities show positive and encouraging outcomes, significantly improving participants' understanding of medicinal plants. Most participants who participated in these activities are intensely interested in further exploring medicinal plants, with some even considering pursuing a career in this field. Despite the high level of interest, several challenges still need to be addressed in harnessing the potential of medicinal plants, including limited scientific research, insufficient educational resources, and regulatory hurdles. Overall, with the appropriate approach and cross-sector collaboration, medicinal plants have substantial potential to become a new cornerstone in the healthcare and economic sectors in North Sumatra and throughout Indonesia. Initiatives like these promotions were expected to serve as a promising initial step in uncovering and realizing this potential. With increased understanding and interest among the younger generation in medicinal plants, they can actively contribute to the sustainable development and utilization of these valuable resources, thereby advancing the healthcare sector and supporting the nation's economic growth.